Redefining Economic Diplomacy: The Growing Role of Non-State Actors in a Changing World - Catalina Bratosin-Vasilache (Ovidius University Annals: Economic Sciences Series)
The field of economic diplomacy has undergone significant transformations in the recent decades, driven by the influence of state actors, but mostly by the continuously expanding role and presence of the non-state actors. While the traditional diplomacy has long been the domain of sovereign states, the rise of multinational corporations, non-governmental organizations and other non-state entities has reshaped the way international relations are being conducted. The purpose of this article is to explore the amplifying role of non-state actors in economic diplomacy, examine their influence over activities such as trade or foreign direct investments and highlight the challenges faced by the state actors in adapting to the current complex international context. The article also emphasizes the need for a more inclusive and adaptive approach to economic diplomacy in the contemporary world, characterized by global crises that may impact or amplify certain trends.